Prosthetic Survival and Complication Rate of Single Implant Treatment in the Periodontally Healthy Patient after 16 to 22 Years of Follow‐Up. (5th September 2014) - Dierens, Melissa; De Bruyn, Hugo; Kisch, Jenö; Nilner, Krister; Cosyn, Jan; Vandeweghe, Stefan
Abstract: Background: Single implants were introduced in the 1980s, but long‐term follow‐up is scarce. Purpose: The study aims to retrospectively investigate the prosthetic survival and complication rates of single implants in periodontally healthy patients after 16–22 years, and to evaluate the influence of different prosthetic procedures. Materials and Methods: Patients with a single implant were recalled for clinical examination. Prosthetic procedures included single‐tooth (ST) and CeraOne (CO) abutments supporting a porcelain‐fused‐to‐metal (PFM), all‐ceramic (CER), or gold‐acrylic (ACR) crown. Prosthetic survival, success, and occurrence of biological, technical, and aesthetic complications were obtained. Procedures were compared by log‐rank tests. Results: Fifty patients attended the examination. All implants were functional; however, 15% of abutments and 27% of crowns had been renewed. Replacements (1/4) were related to technical issues whereas the main cause was aesthetics. The abutment cumulative survival rate (CSR) differed significantly between ST‐PFM (74%), ST‐ACR (0%), and CO reconstructions (97%). The crown CSR was significantly lower for ST‐ACR crowns (0%) compared with ST‐PFM (68%) and CO (81%). Thirty‐nine percent of implants remained complication free throughout the mean 18.5 years. Complications (1/3) required component replacement, and 53% occurred within 5 years after surgery. Conclusion: Prosthetic survival rates of single implants are encouraging after 16 to 22 years. However, 66% of the patients encountered at least one complication during follow‐up.